Assessing Job Satisfaction of Community Pharmacists with the Warr-Cook-Wall Instrument in West Java - Kusumah Wardani, Sintaresmi; Yasin, Nanang Munif; Trung, Vo Quang (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Improving the quality of public health cannot be separated from the role of pharmacists who are responsible for providing pharmaceutical services. Pharmacists' long working hours and great responsibility impact how satisfied they feel with their jobs.Objectives: This study aims to determine the level of job satisfaction and identify the variables that affect community pharmacists' job satisfaction in West Java.Methods: A cross-sectional study conducted in mid-December 2022 to mid-February 2023 with research subjects community pharmacists working in pharmacies, primary health centers or clinics in the West Java region. A convenience sampling technique was used for selecting a community pharmacist. This study involved 145 community pharmacists and used a semi-structured questionnaire, Warr-Cook-Wall satisfaction scale and implemented the Likert scale to describe pharmacists’ job satisfaction of community pharmacists in West Java. The analysis used is univariate analysis (descriptive and distribution analysis) and bivariate analysis (multiple regression linear analysis).Results: Most community pharmacists in West Java are more satisfied with the variables in the intrinsic factor (3.0±0.66) than extrinsic factors (3.0±0.70). However, their satisfaction is still low on recognition (2.9±0.7) and income (2.7±0.8). Community pharmacists' job satisfaction is influenced by pharmacy ownership type (p=0.04) and working hour (p=0.05). The regression analysis indicates that working hour had negatively influenced job satisfaction.Conclusion: Community pharmacists feel satisfied with their job, and their satisfaction level is affected by pharmacy working hours.